The Role Paskibra Extracurricular in Developing Students` Social Skills - Astuti, Rizky Dwi (Universitas Pendidikan Indonesia, 2020)
This study aims to describe the role of Paskibra extracurricular in an effort to develop students' social skills seen from indicators of social skills, namely the ability to help each other, the ability to lead and be led, the ability to cooperate, the ability to respect others, the ability to obey rules (discipline), the ability to handle responsibility, the ability to convey opinion, the ability to be a responsive listener, and the ability to confidently ask questions. This study uses a qualitative approach with descriptive research methods implemented at SMPN 45 Bandung. The data in this study were obtained from observation, interviews, documentation studies and literacy studies. The results of the study indicate that Paskibra can play a role in developing students' social skills through various activities carried out by Paskibra extracurricular, namely routine training activities that are able to develop responsible and disciplined attitudes; the activity of providing Paskibra materials that can foster a sense of love for the homeland and nationalism; the participation of students in competitions that can foster students to help each other, cooperate, and be brave; joint training activities that can train communication skills, confidence and mutual respect; Diklatsar activities that can develop the spirit of leadership and cooperation, as well as social service activities that can instill social caring and empathy. Participants students who follow Paskibra extracurricular have good social skills. This can be seen from the change in the positive attitude of students towards the surrounding environment.